The introduction of a safety checklist in two UK hospital emergency departments: A qualitative study of implementation and staff use. Issue 7 (30th January 2020) - Stone, Tracey; Banks, Jon; Brant, Heather; Kesten, Joanna; Redfern, Emma; Remmers, Ann; Redwood, Sabi
Abstract: Aims and objectives: To explore the extent to which a checklist designed to support patient safety in hospital Emergency Departments was recognised and used by staff. Background: Patient crowding in UK Emergency Departments makes it difficult for staff to monitor all patients for signs of clinical deterioration. An Emergency Department Safety Checklist was developed at a UK hospital to ensure patients are regularly monitored. It was subsequently implemented in six hospitals and recommended for use across the National Health Service in England. Methods: This was a qualitative study in two UK hospital Emergency Departments. Data collection consisted of sixty‐six hours of nonparticipant observation and interviews with twenty‐six staff. Observations were sampled across different days and times. Interviews sampled a range of staff. Data were analysed thematically. The study was undertaken in accordance with COREQ guidelines. Results: Staff described the Emergency Department Safety Checklist as a useful prompt and reminder for monitoring patients' vital signs and other aspects of care. It was also reported as effective in communicating patient care status to other staff. However, completing the checklist was also described as a task which could be overlooked during busy periods. During implementation, the checklist was promoted to staff in ways that obscured its core function of maintaining patient safety. Conclusions: The Emergency Department Safety Checklist can support staff in maintaining patient safety. However, it was not fully recognised by staff as a core component of everyday clinical practice. Relevance to clinical practice: The Emergency Department Safety Checklist is a response to an overcrowded environment. To realise the potential of the checklist, emergency departments should take the following steps during implementation: (a) focus on the core function of clinical safety, (b) fully integrate the checklist into the existing workflow and (c) employ a departmental team‐based approach to implementation and training.